Public Speaking sebagai Upaya Branding Guru JSIT Bina Insani Kota Semarang: Public Speaking as Branding for Teachers at JSIT Bina Insani Kota Semarang - Karima, Festi Himatu; Hidayat, Nur; Kustantinah, Indri; Royana, Ibnu Fatkhu; Nugrahani, Dyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This program emphasizes public speaking training, a crucial skill for educators to enhance their personal branding within the Bina Insani Integrated Islamic School Network. Public speaking skills are essential for educators, as they can be applied in various contexts within the educational setting and the broader teaching community. Data gathered from interviews indicate that numerous instructors continue to experience insecurity and shyness when required to engage in public speaking. Nonetheless, public speaking is obligatory for them. Factors contributing to their lack of confidence include insufficient knowledge and the advantages of learning public speaking skills. This service was conducted in the professional setting of JSIT educators in Semarang City, specifically at SD IT Bina Insani in Semarang City. The methodology employed in this service comprises a pre-test, lecture, training, question-and-answer session, implementation, and post-test.